Expression and localization of human oxytocin receptor mRNA and its protein in chorion and decidua during parturition. - M Takemura; T Kimura; S Nomura; Y Makino; T Inoue; T Kikuchi; Y Kubota; Y Tokugawa; T Nobunaga; S Kamiura (The Journal of Clinical Investigation, 1994)
Oxytocin (OT) is widely used to induce labor in the clinical setting. However, its physiological role in normal human parturition remains unclear. We demonstrated the enhanced expression of OT receptor (OTR) mRNA in chorio-decidual tissue, using the polymerase chain reaction after the reverse transcriptase reaction (RT-PCR) and Northern blot analysis. OTR gene expression in chorio-decidual tissue increased fivefold during the course of parturition. In situ hybridization of fetal membrane revealed the expression of OTR mRNA in maternally derived decidual cells. The OTR mRNA was also detected in fetally derived chorionic trophoblast cells. Immunohistochemistry, using a newly developed anti-OTR monoclonal antibody, demonstrated the distribution of OTR protein in fetal membrane. The distribution pattern of OTR protein and OTR mRNA was identical, indicating that the regulation of OTR expression occurs mainly at the transcriptional level. These results support the idea that the expression of decidual OTR regulates the initiation and amplification of labor. The implications of these findings with regard to the pathogenesis of preterm labor are also discussed. Images